Postdocs in Russia: Peculiarities of Employment and Incentives - L. S. Skachkova; I. P. Malichenko; E. A. Yakovleva (Высшее образование в России)
The article presents the results of the author’s research aimed at identifying the peculiarities of employment of postdocs, a relatively new labor category for the Russian academic labor market. Due to several difficulties associated with forming a sample of postdocs (difficulty in identifying key persons responsible for the development of postdoctoral programs; direct, but not always justified, refusals to provide data, difficulties in identifying potential respondents due to their occupation of various scientific positions in Russian universities), the “snowball” method was used. As a result, the empirical basis of the study was formed based on the results of an online survey of 44 postdocs. As part of the study, tasks related to compiling a socio-economic portrait of a postdoc based on economic, socio-demographic characteristics and indicators of research efficiency, identifying the characteristics of the employment and placement experience of postdocs, objective factors and individual motives for making decisions in the field of choosing postdoctoral programs were solved, as well as diagnostics of tools and channels for young researchers to search for vacancies. The authors distinguish between types of academic mobility (educational and labor) and consider postdoctoral studies as a promising form of external labor academic mobility aimed at attracting and retaining high-potential young researchers planning a long-term career in the academic labor market.Shifting the emphasis from the inbreeding model of university development (internal labor mobility) to the model of external labor academic mobility of young specialists allows those universities that can effectively manage the flow of academic human capital to receive additional socio-economic preferences and return on investment. There are very few similar empirical studies that analyze the features of the development of postdoctoral institutions in Russia and abroad and are based on quantitative and qualitative data from surveys of direct participants in external labor academic mobility – postdocs, which determines the scientific novelty and practical value of the proposed results.